2017
DOI: 10.1038/aps.2017.150
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal formula Fuzheng Huayu alleviates CCl4-induced liver fibrosis in rats: a transcriptomic and proteomic analysis

Abstract: Liver fibrosis is a consequence of chronic liver disease that can progress to liver cirrhosis or even hepatocarcinoma. Fuzheng Huayu (FZHY), a Chinese herbal formula, has been shown to exert anti-fibrotic effects. To better understand the molecular mechanisms underlying the anti-fibrotic effects of FZHY, we analyzed transcriptomic and proteomic combination profiles in CCl-induced liver fibrosis in rats, which were treated with extracted FZHY powder (0.35 g·kg·d, ig) for 3 weeks. We showed that FZHY administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…The molecular mechanism involved MAPK, Wnt, and PI3K/Akt signaling pathways via inhibiting c-Jun, p-c-Jun, c-Myc, CCND1, MMP9, P65, p-P65, PI3K, and P38 [ 126 ]. In addition, tanshinone IIA could also work effectively in combination application such as Fuzheng Huayu formula, a well-known Chinese patent medicine used for liver fibrosis, according to a series of high-quality studies [ 127 129 ].…”
Section: Quinonesmentioning
confidence: 99%
“…The molecular mechanism involved MAPK, Wnt, and PI3K/Akt signaling pathways via inhibiting c-Jun, p-c-Jun, c-Myc, CCND1, MMP9, P65, p-P65, PI3K, and P38 [ 126 ]. In addition, tanshinone IIA could also work effectively in combination application such as Fuzheng Huayu formula, a well-known Chinese patent medicine used for liver fibrosis, according to a series of high-quality studies [ 127 129 ].…”
Section: Quinonesmentioning
confidence: 99%
“…The present results were in harmony with the opinion of Naji et al (2017) who confirmed that the changes noted in hepatic cells treated with CCl4 are due to a cellular injury occurring by alteration in membrane permeability resulting from free radicals which in turn resulting from its toxicity. Also, Dong et al (2018) found that microscopic examination of the CCl4-given rat sections exhibited fatty changes along with the increase of inflammatory collections, the loss of normal hepatocytes, obvious collagen deposition and fiber segmentation formation. Moreover, Sahreen et al (2014) reported that CCl4 induction in rats caused DNA fragmentation and histopathological abnormalities.…”
Section: Discussionmentioning
confidence: 93%
“…Rat liver tissues were collected, weighed, and sectioned into small pieces. Then, they were fixed in 4% paraformaldehyde in phosphate buffer and subjected to paraffin embedding for hematoxylin and eosin (H&E) staining, Sirius Red staining, and Masson's staining, according to a previous study [18]. The Masson-stained tissue sections were quantified by ImageJ software (National Institutes of Health, Bethesda, MD, USA).…”
Section: Histopathological Analysis Of Rat Liver Tissuesmentioning
confidence: 99%
“…Since the complexity of CHFs due to their multiple compounds, targets, and biological activities, it has been difficult to assess their real and multiple compounds combined pharmacological effects and mechanisms. Following the recent development of transcriptomics, network pharmacology and systems biology provides novel methodologies for such analyses and a better understanding of the molecular mechanism for different CHFs, like Huangqi decoction [16], Yinchenhao decoction [17], and Fuzhenghuayu formula [18]. They also provide approaches for determining the synergistic effects of active compounds from XYS on liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%